2020
DOI: 10.1001/jamasurg.2020.4112
|View full text |Cite
|
Sign up to set email alerts
|

Needlestick and Sharps Injuries Among Resident Physicians

Abstract: Needlestick and other sharps injuries (NSI) are an important occupational hazard, and approximately 600 000 to 800 000 NSI events were reported annually in US hospital settings as of 1999. 1 These events carry risk of bloodborne pathogen transmission, as well as psychosocial and financial burdens. The cost associated with an NSI could range from $500 to $3000 (as of 2000), depending on the treatment provided. 2 Protecting health care workers against NSIs is an important component of workplace safety, and resid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…A study reported that surgeons are more likely to report needlestick injuries compared to non-surgeons 5) . In addition to orthopedic surgeons, dentists, obstetrics and gynecologists, plastic surgeons and urologists were more likely to incur injuries compared to physicians in internal medicine and emergency medicine 5,16,17) . In an obstetrics and gynecology survey 18) , 57.1% (315/552) experienced the most recent NSI during cesarean section, which was mainly inflicted by someone else (72.4%; 228/315).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study reported that surgeons are more likely to report needlestick injuries compared to non-surgeons 5) . In addition to orthopedic surgeons, dentists, obstetrics and gynecologists, plastic surgeons and urologists were more likely to incur injuries compared to physicians in internal medicine and emergency medicine 5,16,17) . In an obstetrics and gynecology survey 18) , 57.1% (315/552) experienced the most recent NSI during cesarean section, which was mainly inflicted by someone else (72.4%; 228/315).…”
Section: Discussionmentioning
confidence: 99%
“…Studies in the USA and Canada shows a high risk of needlestick injuries among orthopedic surgeons 5,16) . As orthopedic surgeons are greatly exposed to sharp operating tools, suture needles, and fatigue due to long operating hours, they are likely to be at risk of the injuries involving needlestick.…”
Section: Discussionmentioning
confidence: 99%
“…6 Dedicated sharps injuryprevention education sessions that address the need for expedited reporting and treatment and streamlined reporting processes for needlestick and sharps injuries may encourage consistent reporting and lead to improved workplace safety. 5 Some researchers suggest that educational interventions regarding sharps safety can reduce the incidence of sharps injury and increase reporting of injuries; [7][8][9] however, results of a Cochrane systematic review with meta-analysis show that these improvements tend to be small and short-lived. 8 The AORN "Guideline for sharps safety" 1 provides comprehensive recommendations that perioperative teams can implement to reduce the risk of sharps injury in the perioperative setting.…”
mentioning
confidence: 99%
“…In the perioperative setting, the prevalence of needlestick and sharps injuries among medical students and surgical residents who are beginning their clinical experiences has been significant. [5][6][7] In 2020, researchers surveyed 138 surgical residents at one US hospital and found that 68 (49%) had experienced at least one needlestick or sharps injury; the reporting rates for the injuries ranged from 64% for orthopedic surgery residents to 100% for urology and oral-maxillofacial surgery residents. 5 When responding to a question on why they did not report needlestick and sharps injuries, the most common reasons were associated with the amount of nonpatient-care time required for paperwork completion and injury evaluation and treatment.…”
mentioning
confidence: 99%
“…The incidence, risk factors, and prevention of needlestick and sharps injuries have been heavily explored for healthcare professionals and trainees of different specialties. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] For all surgeons in training, 83% reported a needlestick injury. 12 Surgical trainees have been shown to be three times more likely to incur injuries than nonsurgical trainees, with orthopaedic surgery residents being 12 times more likely than the safest specialty, emergency medicine.…”
mentioning
confidence: 99%